Prediction of weight loss of various polyaryletherketones and their composites in three-body abrasive wear situation using artificial neural networks - Harsha A.P.; Nagesh D.S. (My University, 2025)
The objective of the present paper is to investigate the potential of an artificial neural network technique to predict the weight loss of various polyaryletherketones (PAEKs) and their composites in a three-body abrasive wear situation. Back-propagation neural networks have been used to predict the weight loss based on an experimental database in a three-body abrasive wear situation. The results show that the predicted data are perfectly acceptable when compared to the actual experimental test results. Hence a well-trained artificial neural networks (ANNs) system is expected to be very helpful for estimating the weight loss in the complex three-body abrasive wear situation of polymer composites. © SAGE Publications 2007.